2018
DOI: 10.3389/fendo.2018.00299
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Infants With Cryptorchidism and High Risk of Infertility for Optional Adjuvant Hormonal Therapy and Cryopreservation of Germ Cells: Experience From a Pilot Study

Abstract: IntroductionOrchiopexy for congenital cryptorchid testes is recommended between ½ and 1 year of age to preserve testicular germ cell maturation. Early operation is not enough to preserve fertility in 22 and 36% of cases. Aim of this study was to set up a protocol for optional adjuvant hormonal therapy after orchiopexy and thereafter cryopreservation of testicular biopsies from infants with bilateral cryptorchidism and high infertility risk.Materials and methodsWe included 17 boys with bilateral cryptorchidism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…The number of A dark spermatogonia from testicular biopsy at the time of orchiopexy was reported to predict the risk of infertility in adulthood (221,232). Some studies of GnRH administration, before (in most studies) or after orchiopexy or orchiolysis, showed increased fertility indices, as assessed by the number of germ cells or spermatogonia per tubular cross-section or percentage of normal histology from testicular biopsy in childhood, or semen quality (16,231,233,234). To date, there is only one study that reported a long-term effect of hormonal treatment on semen quality in adulthood (235), therefore the combined or sequential surgical and hormonal treatment cannot be recommended as routine practice at this time.…”
Section: Role Of Hormonal Treatment In Cryptorchidismmentioning
confidence: 99%
“…The number of A dark spermatogonia from testicular biopsy at the time of orchiopexy was reported to predict the risk of infertility in adulthood (221,232). Some studies of GnRH administration, before (in most studies) or after orchiopexy or orchiolysis, showed increased fertility indices, as assessed by the number of germ cells or spermatogonia per tubular cross-section or percentage of normal histology from testicular biopsy in childhood, or semen quality (16,231,233,234). To date, there is only one study that reported a long-term effect of hormonal treatment on semen quality in adulthood (235), therefore the combined or sequential surgical and hormonal treatment cannot be recommended as routine practice at this time.…”
Section: Role Of Hormonal Treatment In Cryptorchidismmentioning
confidence: 99%
“…To diagnose these high risks patients, a testicular biopsy at the time of orchidopexy is needed as a supplement to the hormonal profile of serum gonadotropins and inhibin-B [Faure et al, 2016]. This is important, because there is good evidence that patients will benefit from adjuvant LH-RH treatment [Hadziselimovic et al, 2017;Thorup et al, 2018b]. These recommendations have not been adopted in the aforementioned guidelines.…”
Section: Six Months To 1 Year Of Agementioning
confidence: 99%
“…Some patients with syndromic cryptorchidism, as for example patients with Down syndrome or 45,X/46,XY males, will of course remain infertile. However, in cases with genuine gonadotropin insufficiency, early surgical correction is not enough and adjuvant LH-RH treatment should be implemented to improve the fertility potential [Hadziselimovic, 2017;Thorup et al, 2018b]. Cryopreservation may be an option in case of treatment failure of adjuvant LH-RH [Thorup et al, 2018b].…”
Section: Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptorchidism is a common condition resulting in impaired testicular growth, reduction in spermatogonial numbers and impaired germ cell differentiation (Kollin et al 2012), resulting in an increased risk of infertility (Cortes et al 1996). Whilst testicular biopsy for cryopreservation at the time of orchidopexy has been advocated in patients with cryptorchidism (Thorup et al 2018), pre-existing impairment of germ cell development may affect the potential for generating sperm following transplantation. Furthermore, pre-existing impairment to the testicular somatic environment of the recipient testis may prevent further germ cell development.…”
Section: Pre-existing Testicular Pathologymentioning
confidence: 99%